IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INFASTRUKTUR MELALUI PROGRAM SAMISADE TERHADAP KEPUASAN MASYARAKAT DI KECAMATAN CIAWI - Anisa Cikal Febrianti; Abubakar Iskandar; Rusliandy Rusliandy (Universitas Bina Taruna Gorontalo, 2023)
The purpose of research to analyze the implementation from policies through the SAMISADE program and to find out the response of community satisfaction towards infrastructure development in Ciawi District. This is qualitative research with a mixed method type between qualitative and quantitative with Merille S. Grindle's theoretical analysis. The study results show that the 2021 SAMISADE program has completed infrastructure development by village proposals. Infrastructure Development in Ciawi District, as many as 13 villages have completed infrastructure development in 20 construction locations. The condition of the dominant land contour in the Ciawi Subdistrict is in the form of cliffs, so more SAMISADE development funds were absorbed for constructing a Land Retaining Wall (TPT); this function is to stabilize soil conditions. However, there are several obstacles, including from the supervision side of SAMISADE in 2021; there needs to be more supervision in the ongoing development process. Furthermore, the program regulations that will run in 2021 it is considered that the public needs to understand the same as the existing regulations. From the point of view of community satisfaction with this program, it is calculated based on measurement (IKM) with a score obtained with an index number of 91.23, which means service quality A (Very Good). The element of the highest average value (NRR) is the element of Product Specification Type of Service (3.737). The lowest NRR is handling complaints, suggestions, and feedback (3.535). Community ratings are generally good, motivated by the fulfillment of community needs for infrastructure development in the villages of the Ciawi District.